Pengaruh Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF) dan Financing to Deposit Ratio (FDR) Terhadap Profitabilitas pada Bank Umum Syariah yang Terdaftar dalam Statistik Perbankan Syariah OJK Periode 2020–2024 - Meilanie Tri Pratiwi; Fadlillah Ramadhan; Dini Nurhandayani; Kylla Almira Rahma Fadzillah; Alfiana (Indo Publishing, 2026)
This study aims to determine and analyze the effect of the Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and Financing to Deposit Ratio (FDR) on Profitability in Islamic Commercial Banks registered with the Financial Services Authority (OJK) for the 2020-2024 period. Profitability in this study uses the Return on Assets (ROA) ratio. The population used in this study was 14 Islamic Commercial Banks and a sample of 6 samples was taken using a purposive sampling method. Data analysis techniques used in this study were the results of the model selection test, the results of the panel data regression model estimation, the results of the classical assumption test, and the results of the hypothesis test. The results of the analysis from the tests that have been carried out indicate that the Capital Adequacy Ratio (CAR) affects Return on Assets (ROA), Non-Performing Financing (NPF) does not affect Return on Assets (ROA), and the Financing to Deposit Ratio (FDR) affects Return on Assets (ROA). Meanwhile, the results of simultaneous testing showed that the Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and Financing to Deposit Ratio (FDR) had an effect on Return on Assets (ROA).